Improving Stability of Line Inspection Robot During Crossing Jumper Lines With a Centroid Adjustment Adjusting Mechanism - Xiang Yue; Hongguang Wang; Yan Feng; Yong Tian; Wei Wang (IEEE Access, 2022)
The stability of the inspection robot during crossing the jumper lines of the live lines of the 110kV power transmission is very important. In this study, a novel inspection robot was designed, equipped with a centroid adjusting mechanism to increase the stability during crossing the jumper line. The various obstacle crossing modes of the robot and the corresponding planning are designed. The dynamic modeling method for the rigid-flexible coupling of the robot in the flexible cable environment is studied, which helps to understand the influence of the robot on the transmission line in the environment. The simulation is carried out to analyze the deformation of the jumper line when the robot is on it. The results can be utilized to plan the motion to improve the robot’s efficiency and stability when the robot crosses the jumper line.